Front-like expansion and arrest of programmed cell death in brown banana spots. (1st July 2022) - Steinbock, Oliver; Wang, Qingpu; Knoll, Pamela
Abstract: The spot patterns on bananas are a striking case of biological pattern formation and—as a qualitative ripeness indicator—linked to 50 million tons of wasted food per year. Ripening bananas develop these senescent spots as phenolic compounds are enzymatically oxidized and cellular integrity is lost. We characterize the dynamics of the spot expansion and their nucleation rates based on time-lapse movies. Spots nucleate for about 2 days yielding a typical density of 8 spots/cm 2 . The expansion is initially diffusion controlled and the effective diffusion coefficient decreases with nucleation time from 1.3 to 0.4 mm 2 d −1 . During and after expansion, the browning fronts maintain a steep and constant intensity gradient. We quantitatively reproduce these features by a reaction–diffusion model that considers the local oxygen concentration and browning degree of the peel. All model parameters are based on measurements and front stalling is explained by decreasing oxygen levels in the nucleation sites.